Queen ringing vs. queen caging for summer brood interruption - Uzunov, Aleksandar; Chen, Chao; Gabel, Martin; Kovačić, Marin (Informa UK Limited, 2024)
In many temperate regions, increasing temperatures in the autumn and winter result in shorter or even non-existent brood breaks in honey bee (Apis mellifera L.) colonies. This facilitates a year-round reproduction of Varroa destructor and corresponding pathogen pressure. To address this problem, introducing an artificial brood break during winter might be essential. On the other hand, queen caging in summer, as one of the most prominent brood interruption methods, has already been accepted as an effective way for Varroa control in honey bee colonies. In this study, we compared queen caging vs. queen ringing as a novel technique for inducing summer brood interruption.
Keywords: Honey bee, queen, brood interruption, colony development, queen ringing